Toward a global platform for linking soil biodiversity data - Ramirez, Kelly S.; Döring, Markus; Eisenhauer, Nico; Gardi, Ciro; Ladau, Josh; Leff, Jonathan W.; Lentendu, Guillaume; Lindo, Zoë; Rillig, Matthias C.; Russell, David; Scheu, Stefan; St. John, Mark G.; et al. (Frontiers in Ecology and Evolution, 2015)
Soil biodiversity is immense, with an estimated 10-100 million organisms belonging to over 5000 taxa in a handful of soil. In spite of the importance of soil biodiversity for ecosystem functions and services, information on soil species, from taxonomy to biogeographical patterns, is incomplete and there is no infrastructure to connect pre-existing or future data. Here, we propose a global platform to allow for greater access to soil biodiversity information by linking databases and repositories through a single open portal. The proposed platform would for the first time, link data on soil organisms from different global sites and biomes, and will be inclusive of all data types, from molecular sequences to morphology measurements and other supporting information. Access to soil biodiversity species records and information will be instrumental to progressing scientific research and education. Further, as demonstrated by previous biodiversity synthesis efforts, data availability is key for adapting to, and creating mitigation plans in response to global changes. With the rapid influx of soil biodiversity data, now is the time to take the first steps forward in establishing a global soil biodiversity information platform.